Smarter, faster, cheaper : non-boring, fluff-free strategies for marketing and promoting your business - Garland, David Siteman. (Wiley, 2011)
"Save time and money in building. marketing and promoting your businessWith huge recent shifts in the way enterprises are built, marketed, and monetized, these are "wild west" times for business. In this new landscape, entrepreneurs and small business owners actually have an edge in marketing without spinning their wheels or going broke.Smarter, Faster, Cheaper gives you an innovative, approachable new guide on how to market, promote and improve your business drawing on real world examples and offering practical advice as opposed to fluffy theory. It presents a complete roadmap for marketing and promoting your business with the latest techniques. Draws from author David Siteman Garland's extensive experiences as a successful entrepreneurBased on countless interviews with successful leaders, including conversations with entrepreneurs and owners of businesses large and smallStrategies and ideas are easy to understand, digest, and immediately put to useFrom learning when to skimp and when to splurge to mastering the art of online schmoozing, Smarter, Cheaper, Faster will save you time, money, and aggravation whether you're building your tenth business or your first"--